(untitled) - Panda, Niranjan (Wallingford, Con, 1995)
This book presents a broad overview of host plant resistance to insect pests. It shows how plants can defend themselves naturally and how insects have adapted to overcome these mechanisms through coevolution. it also describes screening and breeding for insect resistance. It represents a major advanced textbook for entomologists, plant breeders and all concerned with crop protection
Tương tác giữa cây trồng và dịch hại,Thâm cứu sinh lý và sinh thái côn trùng hại cây trồng,Sinh lý và sinh thái học côn trùng
Keywords: Plants,Insects,Plants,Plant immunochemistry; Insect resistance,Host plants,Hardiness